The Role of the Center for Language Improvement in Enhanching Speaking Skills of The Class One of The Modern Islamic Boarding School Darussalam Gontor at The Girls - Gautama Veri Vetiana (Universitas Islam Negeri Palangka Raya, 2019)
The Modern Islamic Boarding School Darussalam Gontor of the girls 2nd second campus, in conducting the Arabic learning establishes a special section, the center for language improvement, to build a language system and conduct linguistic activities in this boarding school.